Hawking evaporation and superradiant instabilities of primordial black holes in the axiverse of string theory - Coelho, Filipe Miguel Martins Macedo Serrano (2022)
Dissertação de Mestrado em Física apresentada à Faculdade de Ciências e Tecnologia